Safe and effective administration of T-VEC in a patient with heart transplantation and recurrent locally advanced melanoma - Schvartsman, Gustavo (J Immunother Cancer, 2017)
BACKGROUND: Immunotherapy plays a key role in the treatment of metastatic melanoma. Patients with autoimmune conditions and/or on immunosuppressive therapy due to orthotropic transplants, however, are systematically excluded from clinical trials. Talimogene laherparepvec (T-VEC) is the first oncolytic virus to be approved by the FDA for cancer therapy. To our knowledge, this is the first report of T-VEC being administered in the setting of an organ transplant recipient. CASE PRESENTATION: Here we present the case of a patient with recurrent locally advanced cutaneous melanoma receiving salvage T-VEC therapy in the setting of orthotropic heart transplantation. After 5 cycles of therapy, no evidence of graft rejection has been observed to date, and the patient achieved a complete remission, and is currently off therapy. CONCLUSION: This case advocates for further investigation on the safety and efficacy of immunotherapeutic approaches, such as T-VEC, in solid organ transplant recipients.